Advanced Stage Hodgkin Lymphoma: Patient Management - Gini, Guido; Cimminiello, Michele; Galieni, Piero; Hohaus, Stefan; Nassi, Luca; Picardi, Marco; Romano, Alessandra; Tarantini, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Hodgkin lymphoma (HL) is a rare cancer of the lymphoid system. It clinically presents with swollen lymph nodes and/or systemic symptoms, such as fever, night sweats, or weight loss, as signs of a more advanced stage disease. For the purpose of treatment allocation, HL cases are classified as early-stage favorable, early-stage unfavorable, and advanced-stage disease. Here below we describe four different clinical cases from real life that address some key issues and medical needs that are present in the daily practice with patients affected by advanced stage HL. The four clinical cases are quite heterogeneous, but in each case there are strong inputs to manage a specific category of advanced phase HL patient that is going to be treated with first-line therapy.